Flypaper Effect Using SEM and PLS Models - Muhamad Armawaddin (Universitas Negeri Malang, 2018)
This study aims to test and analyse the phenomenon of flypaper effect of local expenditure in Sulawesi province by using SEM and PLS model. Secondary data types use panel data from 81 regencies/municipalities in the period 2016-2017. The specific target of this research is to re-test the symptoms of flypaper effect by using SEM and PLS model. The results showed that by using different analysis model, it still found the flypaper effect of local expenditure shown by the coefficient of influence of transfer fund which is bigger than the coefficient of the influence of Original Income and the influence of indigenous income which is not significant to the expenditure of regency/municipality in Sulawesi. Other local own source revenue is the greatest factor affecting the local own source revenue while the transfer fund is a general allocation fund. Keywords: Flypaper Effect, SEM AND PLS ModelsJEL Classification: H72; C33